The XIAP inhibitor AZD5582 improves the treatment effect of microwave ablation on hepatocellular carcinoma - Wang, Wenhui; Wu, Fuyuan; Wu, Zhe; Zhang, Mengfan; Lu, Qiang (Frontiers in Immunology, 2025)
Background and purposeMicrowave ablation (MWA) is one of the first-line therapy recommended for early-stage hepatocellular carcinoma (HCC). However, the residual tumor, resulting from insufficient ablation, led to recurrence and metastasis of liver cancer. Novel combination strategies are urgently needed to enhance efficiency of MWA.MethodsWe detected the expression of XIAP protein after ablation in primary liver cancer patients using immunohistochemistry. Then, we established in vitro and in vivo IMWA models to further detect XIAP expression. We established an in vitro IMWA model by heating HCC cell lines and, at the same time, applied the XIAP inhibitor AZD5582 and verified the proliferation, migration, and pro-apoptotic ability of the XIAP inhibitor on tumor cells using CCK8, colony formation assay, cell scratch assay, and flow cytometry flow. The IMWA model of C57BL/6 and NTG mice were established, and AZD5582 was used in combination to evaluate the inhibitory and pro-apoptotic effects of different treatment regimens on tumor growth and to detect the local immune infiltration of C57BL/6 tumors. Finally, AZD5582 drug toxicity was detected to confirm its feasibility.ResultsXIAP protein expression is significantly increased in recurrent hepatocellular carcinoma tissues of patients who previously received microwave ablation therapy. In vitro experiments showed that the migration and proliferation ability of HCC cells was significantly reduced, and the level of apoptosis was increased after application of the XIAP inhibitor AZD5582. In vivo experiments further confirmed that ablation combined with the application of AZD5582 significantly reduced the proliferation ability of residual hepatocellular carcinoma. Concurrently, in C57 BL/6 mice with AZD5582 application, the level of local CD8+ T-cell infiltration in the tumor was increased, while the level of Foxp3+ regulatory T-cell infiltration was significantly reduced. The low toxicity of AZD5582 was further confirmed through hematological and pathological examinations of vital organs. These results provide new clues for hepatocellular carcinoma treatment, suggesting the potential role of XIAP inhibitors in hepatocellular carcinoma treatment and their impact in immunomodulation.ConclusionsIn this study, we found that the XIAP inhibitor AZD5582 modulates the immune microenvironment and inhibits the progression of post-ablation residual hepatocellular carcinoma.